Activity of robusta coffee on the expression of CRP and MMP-9 against hyperlipidemia - Prasetya, Rendra Chriestedy; Fatimatuzzahro, Nadie; Jatmiko, Widy (Coffee Science - ISSN 1984-3909, 2020)
Hyperlipidemia especially LDL accumulation causing inflammation in blood vessel. CRP and MMP-9 are component that triggering in inflammation process. This study to know activity of robusta coffee against hyperlipidemia on this component. This study using male wistar rats were divided into three groups ; normal, hyperlipidemia and that were given coffee with high fat diet groups. Robusta coffee was given 3.6x10-6 m3 by intragastric gavage. Blood collection was carried out using infra-orbital for analysis of LDL levels. Furthermore, the experimental animals were sacrificed and coronary arteries were taken for CRP and MMP-9 immunohistochemical staining. Data were analyzed using ANOVA followed LSD test. Results show The highest expression score for CRP and MMP-9 within the hyperlipidemia group was 188.27 ± 1.8 and 277.56 ± 2.1. The decrease in the expression score of CRP and MMP-9 happened within the ones that were given coffee with 59.33 ± 1.5 and 116.7 ± 0.2 each. Results showed that were differences in the expression of CRP and MMP-9 in all groups (p <0.05). In conclusion, activity robusta coffee can decreases the expression of CRP and MMP-9 against hyperlipidemia. Key words: Coronary disease; hyperlipidemia; robusta coffee.